Manuel Afonso do Paço (1895-1968), um arqueólogo no campo da batalha de La Lys (9 de Abril de 1918) - Cardoso, João Luís (2018)
A brief summary of the events personally experienced by Afonso do Paço was presented during his mobilization in France during the First World War. Written by himself on the form of letters, they were later published in a book almost unknown and that the recent commemorations of the battle of La Lys, of which it presents terrible report, like few, completely ignored. These reports were complemented by other elements extracted from several works by the author. The present contribution is thus a tribute paid to him, in the fifty years of his passing and in the hundred years of the end of the bloody conflict in which he had a valiant participation, which earned him public recognition.